1994
DOI: 10.1111/j.1423-0410.1994.tb01661.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Analysis of cDNA Derived from Reticulocyte mRNAs Coding for Rh Polypeptides and Demonstration of E/e and C/c Polymorphisms

Abstract: RNA derived from enriched reticulocytes of Rh-phenotyped donors was isolated, reversely transcribed into cDNA and amplified with Rh-specific primers by polymerase chain reaction. Nucleotide sequence analysis of the entire coding region of the Rh cDNAs was carried out. Four types of cDNAs were identified, tentatively designated as RhSCI, RhSCII, RhSCIII and RhSCIV. Comparison of RhSCII with RhSCI (identical to the previously reported RhIXb/30A cDNA), showed single base pair difference. Since RhSCI and RhSCII we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 17 publications
(8 reference statements)
0
29
0
Order By: Relevance
“…RHC/c polymorphisms were first described by Mouro et al 1 and by Simsek et al 2 They both found a W at amino acid position 16 (G48) on the RHc allele derived from white donors. Also, in the white population in this study, RHc with G48 is the predominant genotype.…”
Section: Discussionmentioning
confidence: 98%
“…RHC/c polymorphisms were first described by Mouro et al 1 and by Simsek et al 2 They both found a W at amino acid position 16 (G48) on the RHc allele derived from white donors. Also, in the white population in this study, RHc with G48 is the predominant genotype.…”
Section: Discussionmentioning
confidence: 98%
“…These amplified sequences included all the nucleotides responsible for the exofacial amino acid differences between the RhD and RhCcEe polypeptides, i.e. amino acids 169, 170, 172, 223, 226, 233, 238, 350, 353, and 354 [13, 21, 22, 23, 24, 25, 26](fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…8 The RhD protein carries the D antigens and the RhCE protein carries the C, c, E, and e antigens. [9][10][11][12][13] A wide genetic diversity exists in RHD and RHCE, resulting in more than 250 RHD and RHCE variant alleles. 14 These variant alleles have been classified into four groups: the partial RHD alleles, alleles encoding the weak D, and D-elution (D el ) phenotypes, the D-null alleles and the RHCE variant alleles, based on their phenotypic expression (see Web resources).…”
mentioning
confidence: 99%